Pembuatan Knowledge Management pada External Cylindrical Grinding - Ikhwan Arief; Muhammad Arieaman Fikri (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
Knowledge management is a process that helps an organization or company in identifying, selecting, preparing, distributing and sending important information and expertise part of an organization or a company to change the behavior or attitude that is not in place. Grinding processes are usually based on the experiences of people who have are experts in their work (tacit knowledge) that will be collected and converted into explicit knowledge so that the information can be maintained and easily accessible.The design began by analyzing the external cylindrical grinding systems and translate them into Unified Modelling Language (UML) which was followed by the design of database and computer software, and test the software. The application software is web-based and can be accessed by multiple users. The application will help the operator in determining parameters with given option of parameter recommendation. The system gives recommendations based on the tacit knowledge that has been gathered into explicit knowledge. The output of the application is a list of selected parameters and report cases. Report data in the case will be used to set up the machine.